A CASE OF HYPOGLYCAEMIA IN A NON-DIABETIC ADULT - Karupiah, Malathi; Kamaruddin, Nor Azmi; Wahab, Norasyikin Abd (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Hypoglycaemia is diagnosed based on the Whipple’s Triad. Nondiabetic adult hypoglycaemia may be related to critical illnesses, drugs, cortisol or glucagon insufficiency, insulinoma or it can be factitious. Post prandial hypoglycaemia may be an early sign of prediabetes. CASE We report a 26-year-old female with recurrent symptomatic hypoglycaemia with symptoms of sweating, giddiness and lethargy for 6 months. She has no known medical illnesses but has a strong family history of type 2 diabetes mellitus. She denies taking traditional medications. The hypoglycaemic symptoms occur after 3-4 hours of her main meals. She had documented glucose level of 1.8-2.8 mmol/L by finger prick testing. The symptoms resolve after consuming sugary drinks. Body mass index was 20 kg/m2 , HbA1c was 4.5%, eGFR 60 ml/min. A prolonged oral glucose tolerance test was performed over 5 hours. At 0 hour her glucose was 4.9 mmol/l, 60 min 10.3 mmol/L, 120 min 8.9 mmol/L and at 5 hours it was 2.8 mmol/L. Her cortisol was 579 nmol/l, insulin level 7.24 uIu/mL (NV 2.6-24.9) and C-peptide 509.3 pmol /L (NV 370- 1470). The occurrence of biochemical hypoglycaemia at 5 hours post OGTT is likely suggestive of inappropriate hyperinsulinemic state of an individual with prediabetes. CONCLUSION Hyperinsulinemic hypoglycaemia is biochemically due to unregulated secretion of insulin from the pancreatic beta cells during low blood glucose levels. This mechanism occurs in prediabetic patients as a counterregulatory effect towards insulin resistance leading to prolonged insulin secretion. Further research is needed to better understand the underlying mechanism.